REMAINING MOTIVATED DESPITE THE LIMITATIONS: SCIENCE TEACHER'S LEARNING PROPENSITY DURING THE COVID-19 PANDEMIC IN THE DEVELOPING COUNTRY - Justin Murwanashyaka; Septian Rafi Abhiyoga; Ranti Ranti (INSECTA: Integrative Science Education and Teaching Activity Journal, 2021)
The COVID-19 pandemic has affected human life at multilevel and is still a tremendous challenge for all sectors of life without exception to education. To cope  COVID-19 effects in education, online teaching and learning was adopted. This study explored how science teachers’ learning remained motivated to teach, despite all the limitations they encountered and endured during the COVID-19 pandemic. This work was carried out in developing county such as Indonesia, Rwanda, Cambodia and Paraguay. The study examines how science teachers’ in developing country have faced obstacle, and meanwhile, despite this, they are still trying their hardest to stay focused on achieving their personal goals during the pandemic. This research is geared by descriptive qualitative approach. Data were collected in series of online survey with thirty nine teachers cross the developing country.  The results showed that the science teachers’ learning with e-learning was less effective because not all teachers and parents of students understood the internet. During the COVID-19 pandemic, teachers are highly required to develop e-learning science learning that can help achieve learning goals, so that e-learning can satisfy all parties, and can reduce its negative impact. Science learning with e-learning can foster educators in mastering digital technology.